2020
DOI: 10.3390/app10051722
|View full text |Cite
|
Sign up to set email alerts
|

Re-Defining, Analyzing and Predicting Persistence Using Student Events in Online Learning

Abstract: In education, several studies have tried to track student persistence (i.e., students’ ability to keep on working on the assigned tasks) using different definitions and self-reported data. However, self-reported metrics may be limited, and currently, online courses allow collecting many low-level events to analyze student behaviors based on logs and using learning analytics. These analyses can be used to provide personalized and adaptative feedback in Smart Learning Environments. In this line, this work propos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 37 publications
(58 reference statements)
0
7
0
Order By: Relevance
“…However, they do not discount the predictability of classical prediction models such as logistic regression. Similarly, a study by Moreno-Marcos et al (2020) in the domain of online education suggests that prediction accuracy is best achieved by random forest followed closely by logistic regression, both achieving higher than eighty percent predictive accuracy. In supervised learning, classical machine learning models such as logistic regression and newer used models, especially random forest, enable greater exploration in advanced learning environments such as online modality.…”
Section: Literature Reviewmentioning
confidence: 97%
“…However, they do not discount the predictability of classical prediction models such as logistic regression. Similarly, a study by Moreno-Marcos et al (2020) in the domain of online education suggests that prediction accuracy is best achieved by random forest followed closely by logistic regression, both achieving higher than eighty percent predictive accuracy. In supervised learning, classical machine learning models such as logistic regression and newer used models, especially random forest, enable greater exploration in advanced learning environments such as online modality.…”
Section: Literature Reviewmentioning
confidence: 97%
“…Persistence, which captures the extent to which a student continues an activity for a long period, is another long-studied characteristic of students [66]. Students' persistence has been measured in different ways: Whitehill et al categorized students as persistent who interacted with the course at least once a week [92], while Crues et al identified three levels of persistence (low, medium, and high) based on the number of weeks students worked in the course [20].…”
Section: Preprocessing and Feature Selectionmentioning
confidence: 99%
“…Sáiz-Manzanares et al [27] introduce a Moodle plug-in, so-called eOrientation, to detect at-risk students, which is used in junction with a learning analytics module, through which both supervised and unsupervised machine learning techniques can be applied. Moreno-Marcos et al [28] propose analyzing and measuring two types of persistence based on students' interactions in online courses: (1) local persistence (based on the attempts used to solve an exercise when the student answers it incorrectly), and (2) global persistence (based on overall course activity/completion). Chaparro-Peláez et al [29] details the architecture design, configuration, and use of the Moodle Workshop Data Extractor application, and proposes an initial validation of the tool based on the current peer assessment practices of a group of learning analytics experts.…”
Section: A Review Of the Contributions In This Special Issuementioning
confidence: 99%